Age-Related Differences in Locomotor Strategies During Adaptive Walking. Issue 4 (4th July 2017) - Lowry, Kristin A.; Sebastian, Katherine; Perera, Subashan; Van Swearingen, Jessie; Smiley-Oyen, Ann L.
ABSTRACT: Simultaneous control of lower limb stepping movements and trunk motion is important for skilled walking; adapting gait to environmental constraints requires frequent alternations in stepping and trunk motion. These alterations provide a window into the locomotor strategies adopted by the walker. The authors examined gait strategies in young and healthy older adults when manipulating step width. Anteroposterior (AP) and mediolateral (ML) smoothness (quantified by harmonic ratios) and stepping consistency (quantified by gait variability) were analyzed during narrow and wide walking while controlling cadence to preferred pace. Results indicated older adults preserved ML smoothness at the expense of AP smoothness, shortened their steps, and exhibited reduced stepping consistency. The authors conclude that older adults prioritized ML control over forward progression during adaptive walking challenges.